2011
DOI: 10.1097/brs.0b013e318204066a
|View full text |Cite
|
Sign up to set email alerts
|

Occult Spinous Process Fractures Associated With Interspinous Process Spacers

Abstract: Interspinous process spacer surgery appears associated with a higher rate of early postoperative spinous process fracture than previously reported. In all cases, in this series, plain radiographs were inadequate to identify fractures because all fractures were initially minimal or nondisplaced, many patients were osteopenic, and the metallic wings of the devices often obscured fractures. Moreover, in most patients, fractures were associated with mild or no acute localized pain. This study suggests that unrecog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 9 publications
0
36
0
4
Order By: Relevance
“…However, there are also studies reporting that the interspinous implants may result in complications, including implant migration and spinous process fracture [4,27,28]. Kim et al [27,29] indicated that degenerative lumbar spondylolisthesis appears strongly associated with the occurrence of spinous process fracture after interspinous process spacer (IPS) surgery. Current kinematic studies indicate that for elderly patients with Grade 1 DLS, not only the shortest ISP distance but also the range of the shortest ISP distance change decreased during active in vivo function of the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies reporting that the interspinous implants may result in complications, including implant migration and spinous process fracture [4,27,28]. Kim et al [27,29] indicated that degenerative lumbar spondylolisthesis appears strongly associated with the occurrence of spinous process fracture after interspinous process spacer (IPS) surgery. Current kinematic studies indicate that for elderly patients with Grade 1 DLS, not only the shortest ISP distance but also the range of the shortest ISP distance change decreased during active in vivo function of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Zucherman et al [9] reported good functional improvement and pain relief after the implantation of interspinous spacers. However, Bowers et al [10] noted that the procedure carried a high rate of complications, which was separately reported by Kim et al [11].…”
Section: Introductionmentioning
confidence: 91%
“…[13591014] Single-level devices were implanted in 343 cases, while two-level IFDs were placed in 41 cases. [13591014] Patients were followed for an average of 23 months, and up to 4 years. [131014]…”
Section: Complications Reoperation Rates and Poor Outcomes Attributmentioning
confidence: 99%
“…[13591014] In the first study, the complication rate for IFD (X-STOP) in 13 patients was 38%. [3] X-STOP devices were implanted at the L4–L5 (nine patients) and at both the L3–L4 and L4–L5 levels (four patients).…”
Section: Complications Reoperation Rates and Poor Outcomes Attributmentioning
confidence: 99%